THE INFLUENCE OF SERVICE QUALITY, PRODUCT QUALITY AND PROMOTION TOWARDS MISS POE VIETNAM EATERY’S CONSUMER LOYALTY AT GWALK SURABAYA - Jessica Laurentia; J. E. Sutanto; Michael Ricky Sondak (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This research entitled “The Influence of Service Quality, Product Quality and Promotion Towards Miss Poe Vietnam Eatery’s Consumer Loyalty at Gwalk Surabaya” has three objectives, namely: (1) Knowing the influence of service quality towards Miss Poe Vietnam Eatery’s consumer loyalty, (2) Knowing the influence of product quality towards Miss Poe Vietnam Eatery’s consumer loyalty, (3) Knowing the influence of promotion quality towards Miss Poe Vietnam Eatery’s consumer loyalty. Miss Poe Vietnam Eatery is a business that is engaged in food that offers Vietnamese food. This study uses quantitative methods. The population in this study are all consumers who have bought Miss Poe Vietnam Eatery products more than once. The sample in this study amounted to 170 respondents. Data was collected using a questionnaire that distributed online. In this study, the data obtained was processed using multiple linear regression analysis using the SPSS program as a tool. The results of this study are: (1) service quality has a significant effect on Miss Poe Vietnam Eatery’s consumer loyalty. (2) product quality has a significant effect on Miss Poe Vietnam Eatery’s consumer loyalty. (3) Promotion has a significant effect on Miss Poe Vietnam Eatery’s consumer loyalty. Keywords: Service Quality, Product Quality, Promotion, Consumer Loyalty.